DIPLOMATIC ASYLUM GIVEN BY MEXICAN STATE TO AN ANTI-TRUJILLISTA (Tzintzun, Revista de Estudios Históricos, 2016)
This article studies the remarkable case of diplomatic asylum given by MexicanState to a Dominican politician who suffered persecution; this asylum was givenin three different occasions in the mid-twentieth century. The research deals withthe repressive situation that was characterized under the dictatorship of RafaelLeonidas Trujillo in the Dominican Republic. It examines the benefits and thenarrow circumstances of the Convention on Latin American asylum. It emphasizeson the Mexican Asylum policies and the Mexican officials that put them intopractice. It shows that there is a well-defined policy which is shaped by individualappreciation, professional attitude and the political will of those who put it intopractice. With the above, this paper attempts to promote in a higher and betterscale of knowledge such an important matter as it is itself the diplomatic Mexicanforeign asylum policy shaped by the Latin American context.
Keywords: diplomatic asylum; Mexican foreign relation; Dominican inner policy